2019
DOI: 10.3991/ijet.v14i19.10968
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Students Scientific Learning Perception and Critical Thinking Skill Using Paper-Based Testing: School and Gender Differences

Abstract: This study aims to describe and test students' perception of scientific learning, students' critical thinking skill level in scientific learning, differences in perception and critical thinking skill level of students based on school differences and gender, and the influence of perception on students' critical thinking skill in scientific approach learning. It involved 206 students from three high schools in Banjarmasin, Indonesia. Quantitative data was obtained from a perception questionnaire and critical thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…However, based on the corrected mean scores, the QASEE learning model has the most potential in upgrading the preservice teachers' critical thinking skills, and then followed by the RQA learning model. This finding is in line with the research results by (Amin et al, 2020;Ichsan et al, 2019;Kwan & Wong, 2015;Mahanal et al, 2019;Prayogi et al, 2019;Sari et al, 2019;Zubaidah et al, 2018) who reported that critical thinking skills could be trained by conditioning individuals in constructivist-based learning environments through the implementation of certain learning models.…”
Section: Learning Models and Critical Thinking Skillssupporting
confidence: 90%
See 1 more Smart Citation
“…However, based on the corrected mean scores, the QASEE learning model has the most potential in upgrading the preservice teachers' critical thinking skills, and then followed by the RQA learning model. This finding is in line with the research results by (Amin et al, 2020;Ichsan et al, 2019;Kwan & Wong, 2015;Mahanal et al, 2019;Prayogi et al, 2019;Sari et al, 2019;Zubaidah et al, 2018) who reported that critical thinking skills could be trained by conditioning individuals in constructivist-based learning environments through the implementation of certain learning models.…”
Section: Learning Models and Critical Thinking Skillssupporting
confidence: 90%
“…Interestingly, it is reported that pre-service teachers' critical thinking skills are still at the medium to low levels (Alkharusi, 2019;Cansoy et al, 2018;Sari et al, 2019). Likewise in Indonesia, some researchers report that pre-service teachers' have critical thinking dispositions (As'ari et al, 2017); and critical thinking skills are still underdeveloped (Saefi et al, 2017;Sari et al, 2019), especially in the aspect of inference (Saefi et al, 2017) and self-regulation (Nuraini, 2017). Moreover, there was a research result showing that more than 40% of pre-service teachers are unsure of their own readiness to teach critical thinking skills to their students in the future (Kusaeri & Aditomo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The schedule was also really designed so that project completion did not exceed the predetermined time limit. In more detail, the third syntax was carried out by conditioning the students to do these following activities: Rediscussing products that had been determined in the previous stage (Sari et al 2019); Completing various product contents from various sources including the internet and expert figures (Bayram et al 2019); discussing in a group and focusing on preparing designs, developing contents, determining tools and materials, compiling time schedules and designing budgets (Somjai & Soontornwipast, 2020); and completing the workbook until the planning stage (Mutakinati et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This model is designed to direct students' thinking, problem-solving, and intellectual skills. The habit of critical thinking in Indonesia itself is carried out through learning activities with a scientific approach by conducting scientific investigations (Wahyudi et al, 2015;Fajrianthi et al, 2016;Agraw et al, 2017;Sari et al, 2019).…”
Section: Problem Based Learning (Pbl)mentioning
confidence: 99%